Prognostic risk factors for complications associated with tibiotalocalcaneal arthrodesis with a nail. Issue 6 (August 2020) - Kowalski, Chris; Stauch, Chris; Callahan, Ryan; Saloky, Kaitlin; Walley, Kempland; Aynardi, Michael; Juliano, Paul
Highlights: Tibiotalocalcaneal (TTC) arthrodesis is an effective salvage procedure for many foot and ankle pathologies. Complications rates are high, however, especially for those with medical comorbidities. Diabetes, diabetic neuropathy, Charcot neuroarthropathy, elevated HbA1C >7.5, and higher ASA classification produce increased risk for complication. Patients with the above comorbidities may require pre-operative optimization, and postoperative protocols may need to be altered to diminish the risk of complication. Abstract: Background: Tibiotalocalcaneal (TTC) arthrodesis with a nail can be an effective salvage procedure for several foot and ankle pathologies, but has a relatively high complication rate. The purpose of this study is to investigate risk factors associated with complications after TTC arthrodesis with a nail. Methods: Clinical and radiographic outcomes for 82 patients from 2012 to 2016 who underwent TTC arthrodesis with a nail were retrospectivelyevaluated to determine if patient or surgeon specific variables offered prognostic value in predicting negative outcomes. Results: Diabetes, diabetic neuropathy, high (>2) American Society of Anesthesiologists (ASA) classification, and Charcot neuroarthropathy all were predictive of developing a nonunion in either the subtalar ortibiotalar joints (p < 0.05). Diabetic neuropathy was predictive ofreoperation, and along with HbA1C >7.5 was also predictive of hardwarefailure. The odds ratio (OR) for diabetic neuropathy was 2.99 (p < 0.05)for nonunion in the tibiotalar or subtalar joints, 3.46 (p < 0.05) for reoperation, and 4.11 (p < 0.05) for hardware failure. High ASAclassification had an odds ratio of 3.93 (p < 0.05) for nonunion in the tibiotalar or subtalar joints as well. Diabetes had an odds ratio of 2.57 (p < 0.05) for nonunion. Conclusions: Patients with diabetic neuropathy, Charcot neuroarthropathy, elevated HbA1C, and ASA classification >2 demonstrated a higher complication rate in patients undergoing TTC arthrodesis with a nail.